2017
DOI: 10.1002/rcr2.221
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax and central vein thrombosis, an under‐recognized association: a case series

Abstract: Chylothorax is defined as the presence of chyle in the pleural cavity. Central vein thrombosis is an under‐recognized cause of chylothorax in the adult population and is commonly related to central venous catheterization. Case 1 illustrates a patient with AIDS and disseminated tuberculosis with left chylothorax and central vein thrombosis after a month of antituberculosis therapy. Case 2 was a patient with advanced seminoma who presented with left chylothorax and central vein thrombosis while on chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Chylothorax is the accumulation of lymphatic fluid in the pleural cavity ( 1 ). Common causes include direct injury of the thoracic duct after surgery or the infiltration of the lymphatic systemic secondary to malignant disease, whereas SVC obstruction represents a rare cause ( 2 , 3 , 4 ). Chylothorax is a frequent complication of CHD surgery, occurring in about 1% to 9% ( 5 ), increasing morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Chylothorax is the accumulation of lymphatic fluid in the pleural cavity ( 1 ). Common causes include direct injury of the thoracic duct after surgery or the infiltration of the lymphatic systemic secondary to malignant disease, whereas SVC obstruction represents a rare cause ( 2 , 3 , 4 ). Chylothorax is a frequent complication of CHD surgery, occurring in about 1% to 9% ( 5 ), increasing morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature, we only identified five cases of transudative chylothoraces in the setting of SVC syndrome , [[8], [9], [10], [11]]. This number is limited by the fact that a majority of the ten cases of chylothorax associated with SVC syndrome do not have PFA detailed in the reports.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, malignancy-related DVT of the left subclavian/brachiocephalic vein was identified as the possible etiology for the bilateral chylothorax. A deep vein thrombosis of the left subclavian vein can lead to pressure in return of the thoracic duct, which can cause leakage into the pleural space [18]. The thoracic duct will drain into the left side of the neck 92-95% of the time, with the final termination site varying between the left subclavian vein and internal jugular vein junction, the internal jugular vein, the external jugular vein, and subclavian vein [19].…”
Section: Discussionmentioning
confidence: 99%